Acute increases in brain-derived neurotrophic factor following high or moderate-intensity exercise is accompanied with better cognition performance in obese adults - Inoue, Daniela Sayuri [UNESP] (2020)
The purpose of this study was to test if different intensities of aerobic exercise could influence abdominal fat, isoforms of BDNF and executive function. Twenty obese men (30.0 ± 5.4 years old; 34.4 ± 3.5 kg/m2) were randomized to moderate-intensity continuous training (MICT, n = 10) and high-intensity intermittent training (HIIT, n = 10) three times a week for 6 weeks, with isoenergetic energetic expenditure for each exercise session (~ 300 kcal) between conditions. Abdominal fat was assessed pre- and post-intervention; executive function (Coding subtest from BETA-III non-verbal intelligence test and Stroop Color and Word Test), concentrations of mBDNF and proBDNF were assessed in response to acute exercise pre- and post-intervention. Abdominal fat did not change in either group. There was a significant increase in mBDNF immediately after acute exercise in both groups before and after intervention. proBDNF did not present changes acutely nor after 6 weeks. Executive function presented a main effect of time at pre- and post-intervention time-points Stroop Word and Stroop Color and Coding subtest presented improved performance from pre- to post-acute exercise session, in both groups. In conclusion, executive function improvements and acute exercise session-induced increases in mBDNF concentration were found from pre- to post-exercise intervention similarly between MICT and HIIT in obese men.